Conceptualising the active welfare subject: welfare reform in discourse, policy and lived experience - Wright, Sharo (Policy and politics, 2016)
The idea of the active welfare subject has become irresistible to both policy makers and academics and has taken a lead role in the transformation of twenty-first century social security systems. Two distinguishable approaches have emerged - the dominant model and a counter model. The dominant model emphasises moralised individual responsibility for 'wrong choices' and mandates behavioural change to become active. The counter model situates benefit recipients in the present as disempowered creative, reflexive and resourceful beings. This article develops conceptualisations by comparing benefit recipients' accounts (from an exploratory qualitative study) of lived experience with both models.